Silicon Ethoxide as reversible surfactant in reversible drilling mud and the mud’s effect on permeability - Emeka Emmanuel Okoro; Adewale Dosunmu; Sunny Iyuke (Journal of King Saud University: Engineering Sciences, 2020)
Decades of innovation, research and improvements have left drilling fluid vastly different from a mixture of water and clay but are now referred to as non-Newtonian fluids. For optimum well performance for new wells, drillers are to make a choice between drilling with pseudo oil based mud to achieve stability in difficult trajectories and risk permeability impairment; or drill with water based drilling fluid and risk possible drilling instability. Reversible emulsion based muds which can be converted using an acid-base chemical switch from water-in-oil (W/O) to oil-in-water (O/W) emulsion have been suggested as solution in literature. The effect of this acid-base chemical-switch reaction with drilling equipment and personnel prompted this study. Silicon Ethoxide was identified and applied in this study because it has the properties of a reversible surfactant and can be used to formulate a reversible mud that will not react with the drilling equipment nor the formation. Different measurements of Silicon Ethoxide were used, ranging from 5 ml to 45 ml, but we achieved reversibility from 30 ml. Three different base oils (EDC-99, Palm Kernel Oil and Polytriethanolamine) were also used. With the reversed emulsion mud systems, reduction in permeability within the range of 16–19 mD which is minimal was recorded. Thus, this mud system can be used close to the reservoir during drilling operation without encountering significant permeability impairment.